The influence of elements of information of police investigation on the motivation of condemnatory criminal sentence: an analysis of the decisions pronounced by criminal courts of Maceió/AL - Sampaio, André Rocha (2020)
This article proposes to present the frequency of use of the police investigation as part of the motivation of judicial decisions coming from the Residual Criminal Courts of Maceió city - Alagoas, in order to unveil the inquisitory and therefore undemocratic functioning of the due criminal process. Starting from an empirical problem question, “is the police investigation used in the motivation of court sentences?” methodological techniques were also adopted: the flow analysis of the criminal justice system and the use of a qualitative and quantitative instrument. To this intent, the development of the research in question was divided into three main moments, namely: the delimitation of the object, the data collection and, finally, the analysis of the collected data. After this investigation, the effective use of the informative elements in the reasoning of the sentences was demonstrated, since in 80.6% of the cases (corresponding to 369 cases) the magistrate expressly used some informative element produced during the preliminary investigations, corresponding, of this total, about 91% (336) of the cases relating to condemnatory judgments. Thus, it converges to the confirmation of the problems that permeate the art. 155 of the Code of Criminal Procedure, when inserted in an essentially inquisitive system.